15-Year follow-up of regional right and left ventricular function after the Senning operation: a Colour-Doppler myocardial imaging study. Issue 7 (2nd November 2021) - Moya, Ana; De Meester, Pieter; Troost, Els; Roggen, Leen; Weidemann, Frank; Moons, Philip; Eyskens, Benedicte; Claus, Piet; Budts, Werner; Van De Bruaene, Alexander
Abstract: Introduction: Despite right ventricular (RV) dysfunction being a major concern in Senning patients, long-term follow-up data is lacking. This study aimed (1) at evaluating regional (base-mid-apex) RV and left ventricular (LV) function using Colour-Doppler myocardial imaging over a 15-year follow-up period and (2) at comparing results with matched controls. Methods: For the longitudinal analysis (2004–2019), we compared systolic and diastolic function in 10 Senning patients. For the cross-sectional analysis, we compared the subaortic RV (sRV) of Senning patients with the RV and LV of matched controls and the subpulmonary LV (spLV) of Senning patients with the LV of matched controls. Results: The longitudinal analysis of sRV function showed a significant decrease in apical peak systolic strain (−17 ± 7% vs −12 ± 4%; p = 0.025) and apical peak systolic strain rate (−1.1 ± 0.3s −1 vs −0.8 ± 0.4s −1 ; p = 0.012). spLV function showed a significant decrease in peak systolic velocity (mid; p = 0.013 and apex; p = 0.011) and peak systolic strain rate (mid; p = 0.048). The cross-sectional analysis revealed significant lower values for basal, mid and apical peak systolic velocity, peak systolic strain rate, peak systolic strain of the sRV of Senning patients when compared to both LV and RV of matched controls (all p < 0.05). Conclusion: Our study showed that systolic and diastolic sRV function did not change over a 15-year follow-up period, except in the apical region. There was a decline in spLV systolic function, which may be of clinical value. On the other hand, when compared to age- and gender-matched controls, the sRV of Senning patients exhibits significantly decreased measurements of longitudinal systolic function.